Pengaruh Kompetensi, Pengalaman Kerja, Gaya Kepemimpinan dan Lingkungan Kerja Pada Kualitas Audit - Putri Erawan, Ni Made Ayu Nirmalasari; Sukartha, I Made (E-Jurnal Akuntansi; Vol 24 No 3 (2018), 2018)
The purpose of this study was to determine the effect of competence, work experience, leadership style and work environment on audit quality. The theory used in this study is agency theory, motivation theory and attribution theory. The population in this study were 53 staff inspectorate and functional auditor position staff as many as 53 people in the Tabanan Regency Inspectorate Office. The number of samples used was 33 respondents with purposive sampling method. Data collection method uses questionnaire. The data analysis technique used to test the hypothesis in this study is multiple linear regression analysis with the SPSS program. The results of the analysis show that competence, work experience, leadership style and work environment have a positive effect on audit quality. To improve audit quality, it is important to pay attention to factors that can influence such as external and internal factors, so that what is produced is in accordance with organizational objectives and is efficient. Keywords: competence, work experience, leadership style, work environment, and audit quality